Mapping the links between Industry 4.0, circular economy and sustainability: a systematic literature review. Issue 1 (3rd February 2022) - Patyal, Vishal Singh; Sarma, P.R.S.; Modgil, Sachin; Nag, Tirthankar; Dennehy, Denis
Abstract : Purpose: The study aims to map the links between Industry 4.0 (I-4.0) technologies and circular economy (CE) for sustainable operations and their role to achieving the selected number of sustainable development goals (SDGs). Design/methodology/approach: The study adopts a systematic literature review method to identify 76 primary studies that were published between January 2010 and December 2020. The authors synthesized the existing literature using Scopus database to investigate I-4.0 technologies and CE to select SDGs. Findings: The findings of the study bridge the gap in the literature at the intersection between I-4.0 and sustainable operations in line with the regenerate, share, optimize, loop, virtualize and exchange (ReSOLVE) framework leading to CE practices. Further, the study also depicts the CE practices leading to the select SDGs ("SDG 6: Clean Water and Sanitation, " "SDG 7: Affordable and Clean Energy, " "SDG 9: Industry, Innovation and Infrastructure, " "SDG 12: Responsible Consumption and Production" and "SDG 13: Climate Action"). The study proposes a conceptual framework based on the linkages above, which can help organizations to realign their management practices, thereby achieving specific SDGs. Originality/value: The originality of the study is substantiated by a unique I-4.0-sustainable operations-CE-SDGs (ISOCES) framework that integrates I-4.0 and CE for sustainable development. The framework is unique, as it is based on an in-depth and systematic review of the literature that maps the links between I-4.0, CE and sustainability.